Association between early dietary patterns and cardiometabolic health at age 8: a confirmatory analysis of the European Childhood Obesity Project - Mariona Gispert-Llauradó; Joaquin Escribano; Natalia Ferré; Veit Grote; Berthold Koletzko; Gina Ambrosini; Elvira Verduci; Dariusz Gruszfeld; Annick Xhonneux; Veronica Luque (Nutrition Journal)
Abstract Background & Aim Metabolic and cardiovascular health outcomes are strongly influenced by diet. Dietary habits established in early childhood may persist into adulthood. This study aimed to examine the association between dietary patterns at both 2 and 8 years of age, explaining the maximum variability of high- and low-quality fats, sugars, and fibre, and cardiometabolic markers at age 8 years. Methods This was a secondary analysis of the European Childhood Obesity Project, formerly a randomized clinical trial across five European countries performed in healthy term newborns. Children in the study were categorized at ages 2 and 8 years into two groups based on cluster analysis of dietary patterns (DP) derived from Reduction Rank Regression (RRR). A cross-sectional and prospective analysis was conducted to evaluate the associations between these DPs and cardiometabolic outcomes, including body mass index (BMI), blood pressure (BP), and biochemical markers. Triglycerides, HDL cholesterol and insulin resistance index (HOMA-IR) were also categorized as altered versus normal values. Asociations between dietary patterns and health outcomes were assessed using linear and logistic regression models, adjusting for covariates based on a step-wise approach. Results A total of 336 children were classified based on quality of nutrient intakes into either a “Poor-Quality dietary pattern” (PQ-DP) (48% and 66% of infants at 2 and 8 years, respectively) or the “Health-Conscious dietary pattern” (HC-DP) (52% and 34% of infants at 2 and 8 years, respectively). Following a PQ-DP at both ages 2 and 8 was associated with higher triglycerides (β = 0.061, p = 0.049), systolic and diastolic BP (β = 13.019, p < 0.001 & β = 7.612, p = 0.014, respectively) and altered levels of HOMA-IR (OR = 3.1, p = 0.037, 95% CI = 1.1–9.1) at 8 years, compared to children with an HC-DP at both ages, after adjusting for confounders. Conclusion Adherence to a dietary pattern with a poorer nutritional profile in early childhood and school age is associated with worse cardiometabolic risk markers at 8 years old.